2012
DOI: 10.1530/erc-12-0242
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes increases the risk of breast cancer: a meta-analysis

Abstract: The aim of this meta-analysis was to collate and analyse all primary observational studies investigating the risk of breast cancer (BC) associated with diabetes. In addition, we aimed to complete subgroup analyses by both type of diabetes and gender of study participants to further clarify the origin of any such association between the two. Studies were obtained from a database search of MEDLINE, EMBASE, PubMed, Current Contents Connect and Google Scholar with additional cross-checking of reference lists. Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 73 publications
6
102
1
7
Order By: Relevance
“…Diabetes is associated with increased breast cancer incidence and mortality (125)(126)(127)(128)(129).…”
Section: Clinical Datamentioning
confidence: 99%
“…Diabetes is associated with increased breast cancer incidence and mortality (125)(126)(127)(128)(129).…”
Section: Clinical Datamentioning
confidence: 99%
“…The contribution of variable pharmacokinetics to these processes is an active area of research (Desta et al, 2011). Although the mechanisms are poorly understood, individuals with type 2 diabetes mellitus have a greater risk of being diagnosed with breast cancer (Hardefeldt et al, 2012). Important next steps for determining the relevance and mechanism of the interaction between t-CA and CYP2A6 include determining the concentration of t-CA (total and unbound) in humans upon oral administration of t-CA and/or cinnamon powder, the influence of cytosolic enzymes on t-CA stability/ potency, and further characterization of CYP2A6 degradation and t-CA metabolism by CYP2A6.…”
Section: Tablementioning
confidence: 99%
“…[7] The effect of diabetes on the prognosis of breast cancer patients has been extensively investigated in recent years. A well-designed meta-analysis showed that women with diabetes had a 23% greater risk of subsequent breast cancer than those without diabetes.…”
Section: Introductionmentioning
confidence: 99%